Moderation of Good Corporate Governance: Agency Cost, Liquidity Ratio, and Leverage on Dividend Policy - Nur Vita Opu; Andi Jenni Indriakati (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study examines and determines the effect of agency cost, liquidity ratio, and leverage on dividend policy with good corporate governance as a moderating variable in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. This research is quantitative. Withdrawal of research hypotheses using agency and signaling theories is supported by previous studies with similar variables. The research object is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for 2019-2021. Research variables include Agency Cost, Liquidity Ratio, Leverage, Good Corporate Governance, and Dividend Policy. The data source used is secondary data from the collection of financial statement documents. The analytical method consists of panel data regression analysis and testing of all hypotheses through moderated linear regression analysis, t-test, and testing of the coefficient of determination with the help of Eviews 12 for data analysis. The results show that partially Agency Cost; Liquidity Ratio has a negative and significant effect on Dividend Policy in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. While Leverage Disclosure partially has a positive and insignificant impact on Dividend Policy in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange.